2004
DOI: 10.1007/s00586-004-0757-6
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative transarterial embolization of vertebral metastases

Abstract: IntroductionSpinal neoplastic lesions of metastatic origin severely affect patient quality of life. Metastasizing tumors show spinal manifestation in 30-70% of cases [2]. Most common primary tumors of vertebral metastases are localized in the breast, lung, prostate and kidney. Surgical intervention with corporectomy, body replacement and stabilization, although controversial, is still the best treatment option for spinal instability, neurological complications and severe pain that cannot be managed conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 8 publications
(12 reference statements)
4
72
2
2
Order By: Relevance
“…Our data indicate that primary tumors and non-RCC metastasis had mean blood losses similar to those of the literature benchmark of approximately 2 L. [3][4][5][11][12][13] RCCs demonstrated a statistically significantly greater blood loss with EBLs approaching 3 L (P ϭ .009). This value is higher than those reported by others; though after subdividing these cases into those undergoing complete or partial embolization, the mean EBL of completely embolized RCCs approximated a value just under 2 L, an amount comparable with that in these previous studies.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our data indicate that primary tumors and non-RCC metastasis had mean blood losses similar to those of the literature benchmark of approximately 2 L. [3][4][5][11][12][13] RCCs demonstrated a statistically significantly greater blood loss with EBLs approaching 3 L (P ϭ .009). This value is higher than those reported by others; though after subdividing these cases into those undergoing complete or partial embolization, the mean EBL of completely embolized RCCs approximated a value just under 2 L, an amount comparable with that in these previous studies.…”
Section: Discussionsupporting
confidence: 74%
“…Multiple case series have demonstrated the effectiveness of preoperative embolization in reducing intraoperative blood loss. [3][4][5][6] While preoperative embolization of RCC has become a standard of care, evidence for embolizing other types of tumors is scarce. Also, technical differences in the embolization procedure, such as the type of embolic agent used, embolizing above and below the tumor, partial-versus-complete embolization, and the time from embolization to surgery, have not been well evaluated.…”
mentioning
confidence: 99%
“…[16,17] In a series of 20 vertebral tumors preoperatively embolized by Guzman et al [17], a trend toward decreased blood loss and intraoperative time was demonstrated. Kato et al [18], found the blood loss to be almost half (1128 ml to 520 ml) with the addition of preoperative embolization (with either coils, NBCA, or PVA) for thoracic metastatic epidural tumors in 20 patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Current best practice guidelines on the management of metastatic renal carcinoma suggest that, prior to any operative intervention on the metastatic deposits, they should undergo pre-operative embolisation to reduce the risk of catastrophic blood loss at the time of surgery. A lot of the published data on this topic are from the 1970s and 1980s [4][5][6][7] ; in 1974, Benati et al concluded that multiple published case series' had successfully demonstrated the effectiveness of pre-operative embolisation. Success rates throughout the literature vary from 37 to 96%, 3,8 with complication rates varying from 1 to 32%.…”
Section: Introductionmentioning
confidence: 99%